Variation in hemolysin A expression between uropathogenic Escherichia coli isolates determines NLRP3‐dependent vs. ‐independent macrophage cell death and host colonization. Issue 6 (14th March 2019) - Murthy, Ambika M. V.; Sullivan, Matthew J.; Nhu, Nguyen Thi Khanh; Lo, Alvin W.; Phan, Minh-Duy; Peters, Kate M.; Boucher, Dave; Schroder, Kate; Beatson, Scott A.; Ulett, Glen C.; Schembri, Mark A.; Sweet, Matthew J.
ABSTRACT: Uropathogenic Escherichia coli (UPEC) is the major cause of urinary tract infections (UTIs). The multidrug‐resistant E. coli sequence type 131 (ST131) clone is a serious threat to human health, yet its effects on immune responses are not well understood. Here we screened a panel of ST131 isolates, finding that only strains expressing the toxin hemolysin A (HlyA) killed primary human macrophages and triggered maturation of the inflammasome‐dependent cytokine IL‐1β. Using a representative strain, the requirement for the hlyA gene in these responses was confirmed. We also observed considerable heterogeneity in levels of cell death initiated by different HlyA +ve ST131 isolates, and this correlated with secreted HlyA levels. Investigation into the biological significance of this variation revealed that an ST131 strain producing low levels of HlyA initiated cell death that was partly dependent on the nod‐like receptor family pyrin domain–containing 3 (NLRP3) inflammasome, with this response being associated with a host‐protective role in a mouse UTI model. When the same ST131 strain was engineered to overexpress high HlyA levels, macrophage cell death occurred even when NLRP3 function was abrogated, and bladder colonization was significantly increased. Thus, variation in HlyA expression in UPEC affects mechanisms by which macrophages die, as well as host susceptibility vs . resistance to colonization.—Murthy, A. M. V., Sullivan, M. J., Nhu, N. T. K., Lo, A. W., Phan, M.‐D., Peters, K. M., Boucher, D., Schroder, K., Beatson, S. A., Ulett, G. C., Schembri, M. A., Sweet, M. J. Variation in hemolysin A expression between uropathogenic Escherichia coli isolates determines NLRP3‐dependent vs . ‐independent macrophage cell death and host colonization. FASEB J. 33, 7437–7450 (2019). www.fasebj.org